2019
DOI: 10.1108/ijssp-06-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of employee engagement in the relationship between organisational cynicism and employee performance

Abstract: Purpose Organisational cynicism (OC) is a growing trend in contemporary organisations. However, its impact on employee performance (EP) remains understudied. The purpose of this paper is to address this gap by investigating its effect on EP. The study also investigates the moderating effect of employee engagement (EE) on the relationship between OC and EP. Design/methodology/approach Primary data are collected through questionnaire from employees (N=200) of various health organisations in Pakistan by employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 81 publications
0
26
0
2
Order By: Relevance
“…It leads to enhanced performance through harmonized teamwork and understanding of business settings (Bevan et al, 1997). The studies of Arslan and Roudaki (2019) identified a significant strong positive correlation between EE and employee performance.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…It leads to enhanced performance through harmonized teamwork and understanding of business settings (Bevan et al, 1997). The studies of Arslan and Roudaki (2019) identified a significant strong positive correlation between EE and employee performance.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Competence is needed in the performance of employees [29][30] [31][32] [33]. Competence describes a combination of behaviours between knowledge, skills, and characteristics needed by employees to effectively demonstrate their role in the organization and appropriate performance within the organization [34][35] [36]. Competence is a set of specific behaviors that can be observed and needed by a person to succeed in performing roles and achieve company goals/targets [37][38] [39].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…CSR initiative is a significant predictor of EE (Rupp et al, 2018) as employees are keen to be part of that organization which has a positive impact on society. Furthermore, EE is a strategic resource (Shuck & Reio, 2011) and a source of employee performance (Macey & Schneider, 2008) because EE is defined as a positive mental state, which motivates employees to engage themselves emotionally and cognitively with their job (Arslan & Roudaki, 2019). Moreover, engaged employees realize the importance of their job and work hard to achieve organizational targets (Ismail, Iqbal, & Nasr, 2019), which results in high performance.…”
Section: Introductionmentioning
confidence: 99%